2016
DOI: 10.1111/den.12756
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of bowel cleansing using low‐volume polyethylene glycol with ascorbic acid before pediatric colonoscopy: A pilot study

Abstract: Same-day regimen of polyethylene glycol solution with ascorbic acid is effective and safe for bowel cleansing in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Newer PEG-ELS preparations now contain ascorbic acid; this is more palatable and has a higher osmotic effect, allowing for half the required volume. A pilot retrospective study showed this to be an effective regimen in pediatrics, though these patients also received a dose of sodium picosulfate (13). PEG 3350 without electrolytes (e.g., Miralax R , Bayer Healthcare, Whippany, NJ), originally used for management of constipation and fecal impaction, is now the most commonly used bowel preparation.…”
Section: Polyethylene Glycolmentioning
confidence: 99%
“…Newer PEG-ELS preparations now contain ascorbic acid; this is more palatable and has a higher osmotic effect, allowing for half the required volume. A pilot retrospective study showed this to be an effective regimen in pediatrics, though these patients also received a dose of sodium picosulfate (13). PEG 3350 without electrolytes (e.g., Miralax R , Bayer Healthcare, Whippany, NJ), originally used for management of constipation and fecal impaction, is now the most commonly used bowel preparation.…”
Section: Polyethylene Glycolmentioning
confidence: 99%
“…Newer PEG-ELS preparations now contain ascorbic acid; this is more palatable and has a higher osmotic effect, allowing for half the required volume. A pilot retrospective study showed this to be an effective regimen in pediatrics, though these patients also received a dose of sodium picosulfate ( 13 ).…”
Section: Types Of Bowel Preparationmentioning
confidence: 99%
“…The drug of choice for bowel preparation is polyethylene glycol (PEG) due to its high efficacy, safety, and ease of use, as confirmed by several studies. Both adult and child guidelines recommend PEG as the preferred laxative for bowel preparation ( Pashankar et al., 2004 ; Safder et al., 2008 ; Pall et al., 2014 ; ASGE Standards of Practice Committee et al., 2015 ; Tsunoda et al., 2017 ; Mytyk et al., 2018 ). Split-dose PEG is commonly used for bowel preparation in adults before colonoscopy ( Samarasena et al., 2012 ; Zawaly et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%